LEGAL PROTECTION OF THE RIGHTS OF CHILDREN WHOSE PARENTS LEFT AWAY TO WORK IN FARMING - Yongky Indriawan; Diyan Isnaeni; Suratman (Pena Cendekia Insani, 2025)
This study focuses on legal protection of the rights of children left behind by parents who migrate economically for farming, with case studies in Soki Village, Ncera Village, and Diha Village, Bima Regency. In this context, children often experience indirect care that has the potential to ignore the fulfillment of their basic rights, such as the right to education, protection, and affection. This study uses a normative legal approach with legislative and case approach techniques, and is analyzed in a juridical-qualitative manner. Data were obtained through literature studies and documentation of national regulations, international conventions, and relevant scientific literature. The results of the study indicate that there is a gap between applicable legal norms and their implementation in the field. Legal protection for children in this situation has not been effective, especially due to the absence of a monitoring mechanism that is adaptive to seasonal migration patterns. The implications of this study emphasize the urgency of establishing a community-based protection system and regional policies that are responsive to indirect care patterns in agrarian areas. In addition, there needs to be cross-sector integration between village governments, educational institutions, and child protection institutions to ensure the fulfillment of children's rights in a sustainable manner.